A facile synthesis of a carbon-encapsulated Fe3O4 nanocomposite and its performance as anode in lithium-ion batteries - Prakash, Raju; Fanselau, Katharina; Ren, Shuhua; Kumar Mandal, Tapan; Kübel, Christian; Hahn, Horst; Fichtner, Maximilian (Beilstein Journal of Nanotechnology, 2013)
A carbon-encapsulated Fe3O4 nanocomposite was prepared by a simple one-step pyrolysis of iron pentacarbonyl without using any templates, solvents or surfactants. The structure and morphology of the nanocomposite was investigated by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Brunauer–Emmett–Teller analysis and Raman spectroscopy. Fe3O4 nanoparticles are dispersed intimately in a carbon framework. The nanocomposite exhibits well constructed core–shell and nanotube structures, with Fe3O4 cores and graphitic shells/tubes. The as-synthesized material could be used directly as anode in a lithium-ion cell and demonstrated a stable capacity, and good cyclic and rate performances.
Keywords: electrochemistry; iron oxide; lithium-ion battery; nanoparticles; pyrolysis

(untitled) - Tarascon, J.-M.; Armand, M. (Nature, 2001)

(untitled) - Brown, S.; Pyke, D.; Steenhof, P. (Energy Policy, 2010)

(untitled) - Guo, Y.-G.; Hu, J.-S.; Wan, L.-J. (Adv. Mater., 2008)

(untitled) - Coey, J. M. D.; Berkiwitz, A. E.; Balcells, L.; Putris, F. F.; Parker, F. T. (Appl. Phys. Lett., 1998)

(untitled) - Poizot, P.; Laruelle, S.; Grugeon, S.; Dupont, L.; Tarascon, J.-M. (Nature, 2000)

(untitled) - Ren, S.; Prakash, R.; Wang, D.; Chakravadhanula, V. S. K.; Fichtner, M. (ChemSusChem, 2012)

(untitled) - Muraliganth, T.; Murugan, A. V.; Manthiram, A. (Chem. Commun., 2009)

(untitled) - Wang, S.; Zhang, J.; Chen, C. (J. Power Sources, 2010)

(untitled) - Ji, L.; Tan, Z.; Kuykendall, T. K.; Aloni, S.; Xun, S.; Lin, E.; Battaglia, V.; Zhang, Y. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Jin, S.; Deng, H.; Long, D.; Liu, X.; Zhan, L.; Liang, X.; Qiao, W.; Ling, L. (J. Power Sources, 2011)

(untitled) - Wang, J.-Z.; Zhong, C.; Wexler, D.; Idris, N. H.; Wang, Z.-X.; Chen, L.-Q.; Liu, H.-K. (Chem.–Eur. J., 2011)

(untitled) - Mahmoudi, M.; Sant, S.; Wang, B.; Laurent, S.; Sen, T. (Adv. Drug Delivery Rev., 2011)

(untitled) - Laurent, S.; Forge, D.; Port, M.; Roch, A.; Robic, C.; Elst, L. V.; Muller, R. N. (Chem. Rev., 2008)

(untitled) - Prakash, R.; Mishra, A. K.; Roth, A.; Kübel, C.; Scherer, T.; Ghafari, M.; Hahn, H.; Fichtner, M. (J. Mater. Chem., 2010)

(untitled) - Prakash, R.; Wall, C.; Mishra, A. K.; Kübel, C.; Ghafari, M.; Hahn, H.; Fichtner, M. (J. Power Sources, 2011)

(untitled) - Liu, S.; Tang, X.; Mastai, Y.; Felner, I.; Gedanken, A. (J. Mater. Chem., 2000)

(untitled) - Yin, S.; Shen, P. K.; Song, S.; Jiang, S. P. (Electrochim. Acta, 2009)

(untitled) - Lefrant, S.; Baltog, I.; Baibarac, M.; Schreiber, J.; Chauvet, O. (Phys. Rev. B, 2002)

(untitled) - de Faria, D. L. A.; Silva, S. V.; de Oliveira, M. T. (J. Raman Spectrosc., 1997)

(untitled) - Chen, L. Y.; Zhao, C. L.; Zhou, Y.; Peng, H.; Zheng, Y. Y. (J. Alloys Compd., 2010)

(untitled) - Sing, K. S. W.; Everett, D. H.; Haul, R. A. W.; Moscou, L.; Pierotti, R. A.; Rouquérol, J.; Siemieniewska, T. (Pure Appl. Chem., 1985)

Analytical Methods in Fine Particle Technology; Micromeritics Instrument Corporation - Webb, P. A.; Orr, C. (Norcross, 1997)

(untitled) - Wang, D.-W.; Li, F.; Liu, M.; Lu, G. Q.; Cheng, H.-M. (Angew. Chem., Int. Ed., 2007)

(untitled) - Wang, L.; Yu, Y.; Chen, P. C.; Zhang, D. W.; Chen, C. H. (J. Power Sources, 2008)